À la recherche d’une technique oubliée, le grappage - Régis Aranda; Paul Benoit; Joséphine Rouillard; Anne-Cécile Turquety (Les Nouvelles de l’Archéologie, 2009)
The “grappage” is a forgotten technique of the treatise on forging mill and history of the metallurgy, which consists in throwing in a strongly heated hearth iron parts, generally scraps, and bringing them up to high temperature in order to agglomerate them by welding. This operation is always practised by certain blacksmiths, as well in Europe in Africa or in Japan. For better understanding its use in medieval times, in particular to form large-sized artefacts, bars or anvils, starting from blooms or from scraps, experiments took place since 2007 on the site of the Cistercian abbey of Fontenay. The results obtained are very promising: outlines of anvils and bars could be produced. But, the method of sorting the fragments of blooms requires to be developed, too many slags prevented the “grappage” of a forgeable product during our experiments.